The Mayor of Casterbridge - Hardy, Thomas (Limassol, Cyprus :Burlington, 2013)
Unemployed farmer Michael Henchard, his wife Susan and their baby daughter arrive at a samll town, looking for work. Stopping to eat and rest, Michael gets drunk. The couple argue, and in a drunken state, Michael impulsively auctions his wife and daughter- an act he bitterly regrets the next day. Promising to abstain from alcohol for 21 years, Henchard tries to atone for this terrible act. He works hard, succeeds and becomes respectable . But 20 years later, two women come to Casterbridge looking for him. It is Susan Henchard and her daughter. What will happen now?
BAC
Keywords: Lingua inglesa; Misterio